Vibration characteristics of rotor-bearing system with angular misalignment and cage fracture: Simulation and experiment. (1st January 2023) - Wang, Pengfei; Yang, Yang; Ma, Hui; Xu, Hongyang; Li, Xu; Luo, Zhong; Wen, Bangchun
Highlights: A 5-DOF bearing force model considering misalignment and cage fracture is proposed. The effect of cage fracture on radial and axial vibration of the rotor is studied. The effect of bearing clearance and load on cage fracture vibration is analyzed. The experimental study on the cage fracture of rolling bearing is carried out. Abstract: The rolling bearing misalignment may lead to fracture failure of the cage. However, the research on the vibration response of the rotor system caused by bearing misalignment and cage fracture has not attracted enough attention. In this paper, the vibration characteristics of cage fracture fault are studied from two aspects of simulation and experiment. Firstly, a five-degree of freedom nonlinear bearing force model with the bearing misalignment and cage fracture fault is given. Secondly, the bearing restoring force model is introduced into the rotor finite element model. Then, the dynamic model of the deep groove ball bearing-rotor system is established. The effects of key parameters such as cage fracture degree, radial load, and bearing clearance on the vibration characteristics of the system are simulated and analyzed. Thirdly, the bearing test pieces with real cage fatigue fracture fault are obtained by carrying out the bearing life cycle test. On this basis, the vibration signals of bearing with cage fracture under different loads are collected. The simulation and test results show that the system amplitude increases when cage fracture occurs. The obvious impact vibration characteristics appear in the time domain waveform. The vibration energy gradually concentrates to low-frequency vibration. The frequency components related to cage frequency, such as nf c and nf r ± mf c can be more obviously observed in the envelope spectrum. The results can provide a useful reference for the identification and diagnosis of rolling bearing misalignment and cage fracture.